Fermion geometry and the renormalization of the Standard Model Effective Field Theory - Benoît Assi; Andreas Helset; Aneesh V. Manohar; Julie Pagès; Chia-Hsien Shen (Journal of High Energy Physics, 2023)
Abstract The geometry of field space governs on-shell scattering amplitudes. We formulate a geometric description of effective field theories which extends previous results for scalars and gauge fields to fermions. The field-space geometry reorganizes and simplifies the computation of quantum loop corrections. Using this geometric framework, we calculate the fermion loop contributions to the renormalization group equations for bosonic operators in the Standard Model Effective Field Theory up to mass dimension eight.